Medical and interventional therapy of Kasabach-Merritt phenomenon associated with Kaposiform hemangioendothelioma: A case report - Yan Zhao; Ji Cheng (Journal of Interventional Medicine, 2023)
An infant with Kasabach-Merritt Phenomenon (KMP) presented with a giant subcutaneous mass in the right lower limb, severe hypofibrinogenemia, and thrombocytopenia. Glucocorticoids, along with supportive treatments including transfusion of blood products and clotting factors, were administered to reverse fatal disseminated intravascular coagulation and acute hemolysis. The glucocorticoid dose was tapered slowly, and sirolimus was added to treat the hemangiomas. The patient subsequently underwent interventional therapy. After 6 months of medical and interventional therapy, the patient was doing well with a normal platelet count, the tumor volume was markedly reduced, and the primary cutaneous lesion became pale pink. Currently, the patient remains on sirolimus, and no recurrence of thrombocytopenia or further growth of the mass was observed after six months of follow-up.